The Effectiveness of the CIPP Evaluation Model in Science Learning in the Era of the Industrial Revolution 4.0 - Hilmiyati, Fitri; Panggabean, Tongam E; Khoirunnisa, Riza Noviana; Dewanto, Dewanto; Siregar, Muhammad Sapril; Santosa, Tomi Apra (LPPM Universitas Pahlawan Tuanku Tambusai, 2024)
This study aims to determine the effectiveness of the CIPP model in evaluating science learning in students in the 4.0 revolution era. This research is a type of quantitative research with a meta-analysis approach. The inclusion criteria in this study are 1) the research was published in 2022-2024; 2) research must be indexed by the Science Technology Index (SINTA) or Scopus; 3) research was obtained through the Google Scholar, Mendeley, and ERIC databases; 4) The research must be relevant and report complete data to calculate the effect size valueâ€”data analysis through statistical analysis with the help of JSAP applications. The analysis results of 20 publications obtained a summary effect size value ( d = 0.861; p < 0.001). Effect size is included in the category of very high effect size.Â These findings conclude that using the CIPP model has a positive effect on the evaluation of science learning in students compared to other evaluation models. No publication bias was found in this meta-analysis study, so it can be scientifically accounted for.